Simultaneous Determination of Six Chromones in Saposhnikoviae Radix via Quantitative Analysis of Multicomponents by Single Marker - Jinhua Zhang; Luxiao Chen; Junna Qiu; Yu Zhang; Lu Wang; Lijuan Jiang; Yanyan Jiang; Bin Liu (Journal of Analytical Methods in Chemistry)
A method, quantitative analysis of multicomponents by single marker (QAMS), was established and fully verified based on high-performance liquid chromatography (HPLC) for simultaneous determination of six chromone indicators of Saposhnikoviae Radix (SR). In the present study, cimifugin (C), 5-O-methylvisamminol (V), hamaudol (H), and their corresponding glycosides, prim-O-glucosylcimifugin (GC), 4′-O-β-D-glucosyl-5-O-methylvisamminol (GV), and sec-O-glucosylhamaudol (GH), were selected as bioactive constituents and indicators for the quality evaluation of SR. GV was chosen as the unique reference standard, and relative correction factors (RCF) between GV and the other five chromones were calculated. The feasibility of QAMS for the analysis of chromones was investigated by comparing with the traditional external standard method (ESM). Furthermore, the method was proven to have accuracy (96.98%–102.50%), repeatability (RSD <3%), stability (RSD <3%), precision (RSD <3%), and desirable linearity (R2 ≧0.9999). Subsequently, 55 batches of commercial SR from different regions were determined by QAMS, and their contents were analyzed by principal component analysis (PCA), correlation analysis, and hierarchical cluster analysis (HCA), respectively. Based on the results, a more refined quality standard of commercial SR was proposed: SR was qualified when the total contents of six chromones were greater than 3 mg·g−1. Furthermore, SR could initially be regarded as a superior medicine when it satisfied both conditions at the same time: the total content of GC, C, GV, V, GH, and H was greater than 8 mg·g−1, and the proportion of the total content of C, V, and H was greater than 10%. This study demonstrated that the quality of SR could be successfully evaluated by the developed QAMS method; meanwhile, valuable information was provided for improving the quality standard of SR.